Output Signal Power Analysis in Erbium-Doped Fiber Amplifier with Pump Power and Length Variation Using Various Pumping Techniques. (26th November 2013) - Semmalar, S.; Malarkkan, S.
Abstract : The scope of this paper is to analyze the output signal power with pump power and length variation in cascaded EDFA simulation model performance. This paper describes the simulation model of Erbium-Doped Fiber Amplifier (EDFA) of variable lengths (10 m, 50 m, and 120 m) with dual pumping techniques (dual forward pumping with two 980 nm wavelengths, dual forward and backward pumping with two 980 nm wavelengths) and Tri-pumping techniques. The simulation models consist of input source and pump power coupled by WDM coupler which gives optimized signal power in the above-mentioned simulation model. The simulation model consists of source with multiple wavelengths (1520 nm–1618 nm), pumping source with the wavelength 980 nm, isolator, and filter. The resulting models accurately represent EDFA optimized output signal power. Simulation results show that choosing careful fiber length 120 m and pump power 1 W in dual pumping provided 0.07 W optimized output signal power compared to other pumping techniques.